Analysis of the impact of S&OP process and system development on the pulp and paper supply planning and its work tasks - Raitanen, Reima (My University, 2022)
Market instability, for example due to Covid-19 pandemic and other worldwide events, has positioned companies to focus more on forecasting supply and demand. Sales & operations planning is one process for doing this. Process has been used since the late 70s and has been growing since. In accordance with the aforementioned reasons, the aim of the study was to find out how the current organization can support the implementation of the S&OP process and system that supports it. To answer this, following research question has been created; How will the S&OP process and the systems that support it change Supply Planning job descriptions, and operational work? Moreover, research aims to define the current job structure and job descriptions in the Supply Planning team and how the process changes organizational structures. This paper is conducted as qualitative case study. In order to answer the research question, a comprehensive literature review is conducted, and empirical information is collected by interviewing relevant persons (N = 14) within the company. The study also utilizes quantitative and qualitative data from the company’s internal systems. The findings directly related to the research question are that the work tasks of the Supply Planning team do not change at the operational level, otherwise the work tasks of the demand side are moved closer to the sales organization. It has also been suggested that changes are made to the structure of tasks within the team, in which case the team has better resources to support the process. In addition, the research objectives have been met and further action points for improvements are presented. Increasing the current organization's support for the process takes place through development proposals, which are transferring of the role of Demand Planner to sales coordinator or sales planner, launch of Demand Review, launch of Executive S&OP and identification of current challenges. The challenges have also resulted in a proposal for an incentive system for the S&OP team and upper management, as well as a proposal to shorten the cycle in the monthly review period of 3-9 months and quarterly to 3-18 months. The practical implications of the research are significant in terms of developing the process of the case company, both in terms of presenting clear development steps and in terms of raising general awareness. The validity of the research results is supported by the large number and diversity of the interviews in addition to relevant and recent literature reviewed. This study also came from the need for Case company's process research and development. Moreover, because of system development is in progress, the impacts on supply planning team is yet unclear. Hence, the research question remains to be partly unanswered in that regard and thus highlight the need for further studies. Therefore, further studies are required on the perceived benefits of the process and the changes brought about by the system development regarding the operational work maturity and also from the integration of Case's internal actions.

Markkinoiden epävakaus, joka johtuu esimerkiksi Covid-19-pandemiasta ja muista maailmanlaajuisista tapahtumista, on asettanut yritykset keskittymään enemmän kysynnän ja tarjonnan ennustamiseen. Myynnin ja toiminnan suunnittelu on yksi prosessi tämän tekemiseksi. Prosessia on käytetty 70-luvun lopulta lähtien ja sen huomio on kasvanut siitä lähtien. Edellämainittuja syitä mukaillen, tämän tutkimuksen tavoitteena on selvittää, miten nykyinen organisaatio voi tukea S&OP-prosessin ja sitä tukevan järjestelmän käyttöönottoa. Tähän vastaamiseksi on luotu seuraava tutkimuskysymys; Miten S&OP-prosessi ja sitä tukevat järjestelmät muuttavat Supply Planning-tiimin toimenkuvaa ja operatiivista toimintaa? Lisäksi tutkimuksella pyritään määrittelemään Supply Planning -tiimin nykyinen tehtävärakenne ja toimenkuvat sekä miten prosessi muuttaa organisaatiorakenteita. Tämä tutkimus on tehty laadullisena tapaustutkimuksena. Tutkimuskysymykseen vastaamiseksi tehdään kattava kirjallisuuskatsaus ja empiiristä tietoa kerätään haastattelemalla asiaankuuluvia henkilöitä (N = 14) yrityksen sisällä. Tutkimuksessa hyödynnetään myös kvantitatiivisia ja laadullisia tietoja yrityksen sisäisistä järjestelmistä. Suoraan tutkimuskysymykseen liittyvät löydökset ovat, että Supply Planning -tiimin työtehtävät eivät muutu operatiivisella tasolla, mutta kysyntäpuolen työtehtävät siirtyvät lähemmäs myyntiorganisaatiota. On myös ehdotettu, että tiimin sisällä tehtäisiin muutoksia työtehtävien rakenteeseen, jolloin tiimillä on paremmat resurssit tukea prosessia. Lisäksi huomioidaan tutkimustavoitteet ja toimenpiteitä parannuksia varten esitetään. Nykyisen organisaation tuen lisääminen prosessille tapahtuu kehitysehdotuksilla, joita ovat Demand Plannerin roolin siirtäminen myyntikoordinaattorille tai myynnin suunnittelijalle, Demand Review -palaverin käynnistäminen, Executive S&OP -palaverin käynnistäminen ja ajankohtaisten haasteiden tunnistaminen. Haasteiden tunnistus ovat johtaneet myös ehdotukseen S&OP-tiimin sekä johtoryhmän kannustinjärjestelmästä sekä ehdotukseen muuttaa prosessin sykliä kuukausittaisessa tarkastelujaksossa 3–9 kuu-kauteen sekä neljännesvuosittain 3–18 kuukauteen. Tutkimuksen käytännön vaikutukset ovat merkittäviä Case-yrityksen prosessin kehittämisen kannalta sekä selkeiden kehitysaskeleiden esittämisen että yleisen tietoisuuden lisäämisen osalta. Tutkimustulosten pätevyyttä tukee haastattelujen suuri määrä ja monimuotoisuus sekä asiaankuuluvan ja tuoreen kirjallisuuden tutkiminen. Tämä tutkimus tuli Case-yhtiön prosessi-tutkimuksen ja -kehityksen tarpeesta. Lisäksi, koska järjestelmän kehittäminen on käynnissä, vaikutukset toimitusten suunnittelutiimiin ovat vielä epäselviä. Näin ollen tutkimuskysymys jää tältä osin osittain vaille vastausta, mikä korostaa lisätutkimusten tarvetta tältä osin. Näin ollen lisätutkimusta tarvitaan prosessin koetuista hyödyistä ja järjestelmäuudistuksen tuomista muu-toksista operatiiviseen työhön sekä Case-yrityksen sisäisten toimien integroinnista S&OP prosessin osalta.
Keywords: supply chains; forecasts; supply; demand; processes; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management